The perception of a user on factors affecting the price of housing in Negeri Sembilan - Yusdiana, Yazid (2017)
The housing sector is one of the main sectors in the country's development program aimed at enhancing the quality of life of the population, while contributing towards the creation of a happy family, a loving and harmonious society. But we have witnessed the rising prices of homes in the market such as in Kuala Lumpur and Klang which caused some groups to be unable to afford it, especially to the locals. Therefore, locals choose an adjacent state to migrate and buy property or home. Negeri Sembilan is the states that have been affected by the problem. The main objective of this study is to study housing development, identify perceptions users on factors affecting house prices in Negeri Sembilan and analyze the effects of fluctuating housing prices on consumers. Analysis data is obtained through two methods, there are literature review and questionnaire distributions. The Statistical Packages Software for Social Science Computer (SPSS) has been used in the study in analyzing the effectiveness of this concept. Based on the study, it can be noted that the home price parameter in Negeri Sembilan is due to the high demand and the location is among the critical criteria in the purchase of a home. Through user perception of this study, the conclusion is that construction cost and location are the main factors affecting the price of houses in Negeri Sembilan. As well as the effects that affect the consumer is on the cost of living. In conclusion, the local economy, location and development affect housing prices and will have a huge impact on consumers.